WORKSHOP TENTANG ADMINISTRASI PERKANTORAN BAGI GENERASI Z TANJUNG PRIOK JAKARTA UTARA - Ayu Dwi Astuti; Virgo Simamora (Jurnal Abdimas Bina Bangsa, 2024)
This study aims to provide an in-depth understanding of office administration, its importance in optimizing daily operations, and achieving long-term business goals such as customer satisfaction, cost reduction, and increased competitiveness. Research Problem and Objectives The research problem answers the need to prepare the young generation, especially those still in the educational process, to face the challenges of the job market in Society 5.0. Methodology This research uses a community service approach with a workshop method. The workshop consists of literature research, preparation and implementation stages. The methodology includes lectures and detailed discussion sessions for effective dissemination of knowledge. This event provides a platform for students to gain insight into the basic concepts of office administration and their relevance to the modern workplace, aiming to equip participants with the skills and knowledge required in the contemporary job market. Implications This study highlights the importance of office administration in improving daily operations and achieving long-term business goals. This emphasizes the need for young people to acquire skills such as perseverance, creativity and problem solving to succeed in the modern world of work. These findings highlight the influence of various factors, including skills, access to information, and soft skills, in shaping employee quality